2020
DOI: 10.1142/s1094406020500195
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fair Value on the Matching of Revenues and Expenses: The Case of Asset Revaluations

Abstract: Researchers and practitioners have expressed concern that matching has declined over time, as evidenced by a decreasing association between revenues and expenses. They attribute this decline to the shift in financial reporting from a revenue–expense view that emphasizes matching to an asset–liability view that emphasizes the measurement of economic resources that incorporates more fair values. When revenues rise with inflation but the expenses remain tied to historical costs, the two streams tend to diverge. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A PSM procedure utilizing the determinants identified by Barlev et al (2007) can also be found in Costa et al (2020). Their study documents that the association of revenues with expenses is stronger for revaluation firms than nonrevaluation firms.…”
mentioning
confidence: 99%
“…A PSM procedure utilizing the determinants identified by Barlev et al (2007) can also be found in Costa et al (2020). Their study documents that the association of revenues with expenses is stronger for revaluation firms than nonrevaluation firms.…”
mentioning
confidence: 99%